Dynamic Stretching and Ankle Strategy Exercise in Healthy Ageing - Wijianto Wijianto; Nora Eny Zulikha; Agus Widodo; Ekan Faozi; Hafidh Erli Nurdin Pratama; Hana Nuha Kurnia; Rika Ayu Sarah Nirmala; Naila Putri Kasanda (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
The Growing elderly population requires effective strategies to maintain functional capacity and support healthy ageing. Degenerative processes often decline dynamic balance, significantly increasing fall risks and reducing independence in older adults. This study aims to evaluate the effectiveness of combining Dynamic Sretching Exercise (DSE) and Ankle Strategy Exercise (ASE) on dynamic balance among older adults. A Quas experimental study with one group pre test post test design was conducted. Purposive sampling yielded 28 older adults aged 60-70 years at posyandu lansia ngudi was, Karanganyar. The intervention was administeres once a week for eight weeks. Dynamic balance was measured using the Berg Balance Scale (BBS) and analyzed via Wilcoxon Signed Rank Test. The statistical analysis showed a significant improvement in dynamic balance, with the median BBS score increasing from 52.50 at pretest to 55.00 at post test (Z=-3.651, p<0.001). post intervention data revealed that 17 participants experienced positive ranks (increase scores), while 11 remained unchanged, and none deteriorated. The combination of DSE and ASE is significantly increasing the capacity of dynamic balance among older adults, serving as a viable preventive strategy against fall risks in community settings.